Association Between Serum Phosphate Levels and Stroke Risk in Patients Undergoing Hemodialysis: The Q-Cohort Study. Issue 9 (September 2016) - Yamada, Shunsuke; Tsuruya, Kazuhiko; Taniguchi, Masatomo; Tokumoto, Masanori; Fujisaki, Kiichiro; Hirakata, Hideki; Fujimi, Satoru; Kitazono, Takanari
Abstract : Background and Purpose—: The contribution of serum phosphate levels to stroke risk in dialysis patients remains unclear. The present study aimed to elucidate the respective association between serum phosphate levels and the risk of brain hemorrhage or infarction in patients undergoing hemodialysis. Methods—: A total of 3437 patients undergoing hemodialysis were followed up for a median of 3.9 years. The primary outcome was the occurrence of brain hemorrhage or infarction. Patients were divided into 4 groups based on their baseline serum phosphate levels (Q1–Q4). Stroke risk was estimated using a Cox proportional hazards model. Results—: During the follow-up period, 75 patients experienced brain hemorrhage and 139 experienced brain infarction. The risk of brain hemorrhage was significantly higher in the highest (Q4) compared with the lowest quartile (Q1) as the reference value (multivariate-adjusted hazard ratio [95% confidence intervals]: Q1, 1.00; Q2, 1.76 [0.79–4.18]; Q3, 1.99 [0.92–4.67]; and Q4, 2.74 [1.27–6.47]; P =0.077 for trend; hazard ratio for every 1 mmol/L increase in serum phosphate level, 2.07 [1.10–3.81]; P =0.025). In contrast, the risk of brain infarction was significantly higher in Q1 ( P =0.045) compared with Q3 as the reference value (Q1, 1.65 [1.01–2.73]; Q2, 1.35 [0.82–2.25]; Q3, 1.00; and Q4, 1.30 [0.77–2.20]). Conclusions—: Higher serum phosphate levels were associated with an increased risk of brain hemorrhage, whereas low levels were associated with an increased risk of brain infarction in hemodialysis patients. These results suggest the importance of managing serum phosphate levels within an appropriate range in hemodialysis patients. Clinical Trial Registration—: URL:http://www.umin.ac.jp/ . Unique identifier: UMIN000000556. Abstract : Supplemental Digital Content is available in the text.